Risk factors and long-term health consequences of macrosomia：a prospective study in Jiangsu Province,China - Gu, Shouyong; An, Xiaofei; Fang, Liang; Zhang, Xiaomin; Zhang, Chunyan; Wang, Jingling; Liu, Qilan; Zhang, Yanfang; Wei, Yongyue; Hu, Zhibin; Chen, Feng; Shen, Hongbing (Journal of biomedical research, 2012)
We sought to determine risk factors associated with fetal macrosomia and to explore the long-term consequence of infant macrosomia at the age of 7 years.A prospective population based cohort study was designed to examine the associations between maternal and perinatal characteristics and the risk of macrosomia.A nested case-control study was conducted to explore the long-term health consequence of infant macrosomia.The mean maternal age of the macrosomia group was 24.74±3.32 years,which is slightly older than that in the control group（24.35±3.14 years,P = 0.000）.The mean maternal body mass index（BMI） at early pregnancy was 22.75±2.81 kg/m 2,which was also higher than that in the control group（21.76±2.59 kg/m 2,P = 0.000）.About 64.6% of macrosomic neonates were males,compared with 51.0% in the control group（P = 0.000）.Compared with women with normal weight（BMI：18.5-23.9 kg/m 2）,women who were overweight（BMI：24-27.9 kg/m 2） or obese（BMI ≥ 28 kg/m 2）,respectively,had a 1.69-fold（P = 0.000） and a 1.49-fold（P = 0.000） increased risks of having a neonate with macrosomia,while light weight（BMI〈18.5 kg/m 2） women had an approximately 50% reduction of the risk.Furthermore,macrosomia infant had a 1.52-fold and 1.50-fold risk,respectively,of developing overweight or obesity at the age of 7 years（P = 0.001 and P = 0.000）.Older maternal age,higher maternal BMI at early pregnancy and male gender were independent risk factors of macrosomia.Macrosomic infant was associated with an increased predisposition to develop overweight or obesity at the beginning of their childhood.